New pseudoscorpion species (Pseudoscorpiones: Hesperolpiidae) from Lima City, Peru - Cossios, Daniel (2023)
This study describes and illustrates a new species of arachnid, the pseudoscorpion Stenolpium sayrii sp. nov., collected at Pucllana, an archaeological site in the city of Lima, Peru. With this description, the total number of known Stenolpium species worldwide reaches eight, and in Peru specifically, it increases to seven. The discovery of this new species in Peru's most populous city serves as an exemplar highlighting the extensive scope for further research on Peruvian fauna in general, particularly on its arachnids. Publicación registrada en Zoobank/ZooBank article registered: LSIDurn:lsid:zoobank.org:pub:DA2699AA-6710-4B9F-92CF-931725928EB5Acto nomenclatural/nomenclatural act: Stenolpium sayrii Cossios, 2023 LSIDurn:lsid:zoobank.org:act:6EAB65E6-FFC3-4EFF-89AB-9CA37ACE3114